Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Answer/Step-by-step explanation:
Composition functions are functions that combine to make a new function. We use the notation ◦ to denote a composition.
f ◦ g is the composition function that has f composed with g. Be aware though, f ◦ g is not
the same as g ◦ f. (This means that composition is not commutative).
f ◦ g ◦ h is the composition that composes f with g with h.
Since when we combine functions in composition to make a new function, sometimes we
define a function to be the composition of two smaller function. For instance,
h = f ◦ g (1)
h is the function that is made from f composed with g.
For regular functions such as, say:
f(x) = 3x
2 + 2x + 1 (2)
What do we end up doing with this function? All we do is plug in various values of x into
the function because that’s what the function accepts as inputs. So we would have different
outputs for each input:
f(−2) = 3(−2)2 + 2(−2) + 1 = 12 − 4 + 1 = 9 (3)
f(0) = 3(0)2 + 2(0) + 1 = 1 (4)
f(2) = 3(2)2 + 2(2) + 1 = 12 + 4 + 1 = 17 (5)
When composing functions we do the same thing but instead of plugging in numbers we are
plugging in whole functions. For example let’s look at the following problems below:
Examples
• Find (f ◦ g)(x) for f and g below.
f(x) = 3x + 4 (6)
g(x) = x
2 +
1
x
(7)
When composing functions we always read from right to left. So, first, we will plug x
into g (which is already done) and then g into f. What this means, is that wherever we
see an x in f we will plug in g. That is, g acts as our new variable and we have f(g(x)).
g(x) = x
2 +
1
x
(8)
f(x) = 3x + 4 (9)
f( ) = 3( ) + 4 (10)
f(g(x)) = 3(g(x)) + 4 (11)
f(x
2 +
1
x
) = 3(x
2 +
1
x
) + 4 (12)
f(x
2 +
1
x
) = 3x
2 +
3
x
+ 4 (13)
Thus, (f ◦ g)(x) = f(g(x)) = 3x
2 +
3
x + 4.
Let’s try one more composition but this time with 3 functions. It’ll be exactly the same but
with one extra step.
• Find (f ◦ g ◦ h)(x) given f, g, and h below.
f(x) = 2x (14)
g(x) = x
2 + 2x (15)
h(x) = 2x (16)
(17)
We wish to find f(g(h(x))). We will first find g(h(x)).
h(x) = 2x (18)
g( ) = ( )2 + 2( ) (19)
g(h(x)) = (h(x))2 + 2(h(x)) (20)
g(2x) = (2x)
2 + 2(2x) (21)
g(2x) = 4x
2 + 4x (22)
Thus g(h(x)) = 4x
2 + 4x. We now wish to find f(g(h(x))).
g(h(x)) = 4x
2 + 4x (23)
f( ) = 2( ) (24)
f(g(h(x))) = 2(g(h(x))) (25)
f(4x
2 + 4x) = 2(4x
2 + 4x) (26)
f(4x
2 + 4x) = 8x
2 + 8x (27)
(28)
Thus (f ◦ g ◦ h)(x) = f(g(h(x))) = 8x
2 + 8x.
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.